Problem from MK powerful Number 90/PUU- XII/2023 related to article 169 letter Q Number 7 Year 2017 about general election (Election Law) - Daud Yaferson Dollu; Rahman N. Fatima (Dynamics of Politics and Democracy, 2025)
Purpose: This study aims to examine the constitutional role and dynamics of the Indonesian Constitutional Court (MK) in moderating election regulations, ensuring democratic inclusivity, and maintaining public trust. The research focuses on how the MK contributes to upholding constitutional justice, political equality, and fair representation in Indonesia’s electoral system. Research Methodology: The study applies a normative juridical approach supported by doctrinal legal research. Primary data are derived from constitutional provisions, statutory regulations, and Constitutional Court decisions, while secondary data come from academic journals, books, and previous research. A comparative analysis is also used to evaluate Indonesia’s MK alongside similar institutions in other Asian countries. Results: Findings indicate that the Constitutional Court of Indonesia plays a pivotal role in moderating electoral regulations, such as easing strict nomination thresholds and resolving election disputes. These interventions enhance inclusivity and responsiveness in the electoral process, ultimately strengthening public trust in democracy. The analysis also highlights that the MK’s involvement is more significant compared to similar courts in other Asian democracies. Conclusions: The Constitutional Court is central to safeguarding democratic values, ensuring fairness in electoral processes, and upholding constitutional justice. Its active role underscores the importance of constitutional oversight in maintaining legitimacy and stability within Indonesia’s democratic system. Limitations: The study is limited to legal and doctrinal perspectives without empirical fieldwork, which may restrict the analysis of societal perceptions of the MK’s role.. Contribution: This research contributes to constitutional law studies by providing insights into the MK’s function in electoral democracy and offering recommendations for strengthening constitutional justice in emerging democracies.